Anxiety and depression and cognitive coping strategies and health locus of control in patients with ovary and uterus cancer during anticancer therapy - Kulpa, Marta; Ziętalewicz, Urszula; Kosowicz, Mariola; Stypuła-Ciuba, Beata; Ziółkowska, Patrycja (Contemporary Oncology/Współczesna Onkologia, 2016)
Aim of the study : The crisis associated with cancer may contribute to the development of anxiety and depressive disorders. Contemporary psycho-oncology focuses on the psychological determinants of the cancer patientsʼ functioning to find which disease-coping strategies help the healing process, facilitate the establishment of a good therapeutic relationship and the process of adapting to difficult situations. Aim of the study was assess the psychological functioning of patients with cancer of reproductive organs in the cancer-treating process. The practical aim was to develop guidelines for psychological care dedicated to this group of patients. Material and methods : The study was conducted in the Reproductive Organs Cancer Clinic in Institute of Oncology in Warsaw using a questionnaire consisting of: Demographic, Hospital Anxiety and Depression Scale (HADS), Multidimentional Health Locus of Control (MHLC), Cognitive Emotions Regulations Questionaire (CERQ). Results : Seventy-eight patients aged 22 to 82 (average 54) were examined. Investigation of relationships between anxiety and depression and coping strategies showed: positive correlation of anxiety with self blame and rumination, positive correlation of anxiety and depression with catastrophizing, positive correlation of depression with blaming others, negative correlation of anxiety and depression with acceptance and positive refocusing, negative correlation of depression with refocus of planning and putting into perspective. Conclusions : The results of this study indicate that there may be an indirect method of diagnosing anxiety and depression disorders in cancer patients by observing the coping strategies to cope with the difficult situation.